Juvenile Lupus Erythematosus: Fourteen Years of Experience - Funda BAŞTUĞ; Hakan POYRAZOĞLU; Zübeyde GÜNDÜZ; Sebahat TÜLPAR; Ruhan DÜŞÜNSEL (Archives of Rheumatology, 2011)
Objectives: This study aims to describe the main clinical and laboratory features as well as the morbidity and mortality of juvenile systemic lupus erythematosus (JSLE) in Turkish children. Patients and methods: Thirty children (27 girls, 3 boys; mean age at diagnosis 12.3 years; range 3 to 16 years) with JSLE were evaluated retrospectively. All patients met the 1982 American College of Rheumatology revised criteria for the diagnosis of SLE and had shown clinical manifestations of the disease before the age of 16. Results: The mean period of follow-up was 2.9 years (range 2 months-10 years) and the mean duration of symptoms before diagnosis was 3.3 months (range 2 days-2 years). The frequencies of the clinical and laboratory features of the patients were as follows: erythematous malar rash was seen in 17 (56%), discoid rash in one, photosensitivity in 16 (53.3%), oral ulcers in eight (26.7%), musculoskeletal involvement in 26 (87%), serositis in 13 (43%), hematological abnormalities in 21 (70%), renal involvement in 17 (56%), antinuclearantibody positivity in 27 (93%), pulmonary involvement in eight (27%), cardiovascular disease in seven (23%), and central nervous system involvement in seven patients (23%). During the follow-up four patients (13%) died, three of renal failure and one from sepsis. During the study two patients were in remission without treatment and 22 patients were in remission with treatment. Two patients were lost to follow-up. Conclusion: Juvenile systemic lupus erythemathosus is a serious multisystem organ disease. Although JSLE has a high remission rate with early diagnosis and treatment, it still has a significant mortality rate.